Cyberpragmatics : internet-mediated communication in context - Yus, Francisco (Pragmatics & beyond ;, 2011)
Cyberpragmatics is an analysis of Internet-mediated communication from the perspective of cognitive pragmatics. It addresses a whole range of interactions that can be found on the Net: the web page, chat rooms, instant messaging, social networking sites, 3D virtual worlds, blogs, videoconference, e-mail, Twitter, etc. Of special interest is the role of intentions and the quality of interpretations when these Internet-mediated interactions take place, which is often affected by the textual properties of the medium. The book also analyses the pragmatic implications of transferring offline discou.